Design and implement “Defence Key” - Phạm Thị Thanh Thảo; Hồ Dương Huynh; Lê Thị Lan Thanh (Journal of Technical Education Science, 2019)
Besides the positive development of the technological age, living conditions and the quality of life are rising, the problems of social evils, especially violence and abuse of women and children are increasing rapidly. That should be paid much attention to. Whether science and technology help society to limit the evils or not? The authors' approach is to design a device that will help you (especially for women and children) to defend themselves against evil. The lock with self-defense features such as: Buzzer, laser beam, special shape (with pointed tip, serrated shape, ...) to help you protect yourself, the other features are call and send message to their parents, thanks to the "Life 360" application to detect the location of children in danger and rescue in time.